2020
DOI: 10.15252/embj.2020105130
|View full text |Cite
|
Sign up to set email alerts
|

Siwi levels reversibly regulate secondary pi RISC biogenesis by affecting Ago3 body morphology in Bombyx mori

Abstract: Silkworm ovarian germ cells produce the Siwi-piRNA-induced silencing complex (piRISC) through two consecutive mechanisms, the primary pathway and the secondary ping-pong cycle. Primary Siwi-piRISC production occurs on the outer mitochondrial membrane in an Ago3-independent manner, where Tudor domaincontaining Papi binds unloaded Siwi via its symmetrical dimethylarginines (sDMAs). Here, we now show that secondary Siwi-piRISC production occurs at the Ago3-positive nuage Ago3 bodies, in an Ago3-dependent manner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 59 publications
(117 reference statements)
8
41
0
Order By: Relevance
“…Both Vret and DDX43 interconnect Ago3‐piRISC and piRNA‐unbound Siwi in BmN4 cells (Nishida et al , 2020 and this study). We speculated that Vret and DDX43 physically interact with each other through the ping‐pong cycle although such interaction would be transient.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…Both Vret and DDX43 interconnect Ago3‐piRISC and piRNA‐unbound Siwi in BmN4 cells (Nishida et al , 2020 and this study). We speculated that Vret and DDX43 physically interact with each other through the ping‐pong cycle although such interaction would be transient.…”
Section: Resultsmentioning
confidence: 52%
“…Our recent investigations showed that the Tudor domain‐containing protein, Vreteno (Vret), facilitates Ago3‐dependent Siwi‐piRISC production in the ping‐pong cycle (Nishida et al , 2020). Our study also showed that a subset of nuage (germ cell‐specific granules), which we termed Ago3 bodies, are central hubs in the Siwi‐piRISC production.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations